Assessment of Clothing and Textile Skills and Facilities for Inculcating Entrepreneurship in Undergraduate Students in Southwestern Nigeria - Olowookere, Peter Oladipo (NIU Journal of Humanities, 2025)
This study evaluates the state of training facilities, equipment functionality, and garment-construction skills among Clothing and Textiles undergraduates in Southwestern Nigeria, examining how these factors influence entrepreneurial inclination. Data were gathered from 386 students across public universities, polytechnics, and colleges of education using structured questionnaires, yielding a Cronbach's Alpha of 0.825, alongside direct observations. The demographic profile indicated that 57% of respondents were female, and 63. 7% were aged 21–25, with public universities representing 53. 4% of enrolment. Table analyses showed that while key facilities such as university libraries (74.6%) and textile design studios (73.6%) were widely available, critical practical laboratories like clothing construction (53.1%) and pattern drafting (43.3%) laboratories were significantly under-resourced. Equipment-related data indicate a high availability of stitching tools, with sewing machines accessible to 90. 9% of respondents, and over 60% of these machines reported as functioning well; however, pressing and fitting equipment exhibited lower adequacy and functionality ratings. Pearson chi-square tests confirmed statistically significant relationships (p = 0.000) between the availability, adequacy, and functionality of clothing and textile equipment and students' inclination towards entrepreneurial skills. In terms of skill acquisition, students scored a grand mean of 2. 59 (on a 4- point scale), demonstrating strong proficiency in foundational tasks such as taking body measurements (M = 2. 75) and pattern cutting (M = 2. 70), but lower mastery in advanced techniques including garment lining (M = 2. 45) and interfacing (M = 2. 42). Based on these findings, the study strongly recommends targeted investments to upgrade under-resourced laboratories and modernize essential equipment, coupled with curricular enhancements that focus on advanced practical techniques. These measures are critical to improving skill mastery and fostering a robust entrepreneurial disposition among graduates in the competitive clothing and textile industry.